Analytical Modeling and Simulation of SAW Filter Using Concave - M. M. Elsherbini; M. F. Elkordy; A. M. Gomaa (Institute of Advanced Engineering and Science, 2015)
A Simple novel tool has been developed to model and simulate SAW filter devices. GNU Concave; Freeware tool with open source coding has been used to specify a basic model for SAW delay lines and filters. This paper presents a way for obtaining the essential parameters of design and development of SAW devices as insertion loss. Other parameters were also predicted by within the reseach work like the radiation conductance, susceptance, Impedance, Admetance and the Frequency Response. They all calculated and plotted using Mathmatical equations drived from an equivalent model used to simulate our target. A comparision between the simulated device and an experimental puplished one has been achieved.